2008
DOI: 10.1037/a0014173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of affective instability in ecological momentary assessment: Indices using successive difference and group comparison via multilevel modeling.

Abstract: Temporal instability of affect is a defining characteristic of psychological disorders such as borderline personality disorder (BPD) and mood cycling disorders. Ecological momentary assessment (EMA) enables researchers to directly assess such frequent and extreme fluctuations over time. The authors examined 4 operationalizations of such temporal instability: the within-person variance (WPV), the first-order autocorrelation, the mean square successive difference (MSSD), and the probability of acute change (PAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
694
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 526 publications
(706 citation statements)
references
References 45 publications
9
694
1
2
Order By: Relevance
“…20 Variability of nightly scheduling of bedtime and wake time, and of sleep duration was calculated according to methods described by Sanchez-Ortuno et al 21 For each participant, differences between each consecutive measurement (e.g., bedtime night 2 minus bedtime night 1) were calculated and squared, capturing both variability and temporal dependency across time. 22 These values were used to determine differences in mean variability between groups. The square roots of the weighted means are reported.…”
Section: Actigraphymentioning
confidence: 99%
“…20 Variability of nightly scheduling of bedtime and wake time, and of sleep duration was calculated according to methods described by Sanchez-Ortuno et al 21 For each participant, differences between each consecutive measurement (e.g., bedtime night 2 minus bedtime night 1) were calculated and squared, capturing both variability and temporal dependency across time. 22 These values were used to determine differences in mean variability between groups. The square roots of the weighted means are reported.…”
Section: Actigraphymentioning
confidence: 99%
“…Negative affect instability, as measured by the MSSD, has been linked to more severe depression symptoms across several studies and has been identified as a concomitant and early indicator of depression [22,29,[31][32][33][34]. It has been shown to be a significant risk factor for more frequent and severe suicidal ideation [33] and may be a unique underlying emotion pattern in depression.…”
Section: The Emotion Dynamics Of Depressionmentioning
confidence: 99%
“…This time-structured measure of variability uses the temporal ordering of measurements to quantify the magnitude of incremental changes in emotion [28][29][30]. Crucially, unlike iSD where the same result would be obtained if the same set of emotion expression observations are shuffled through time, the MSSD is sensitive to the time-ordering of observations.…”
Section: The Emotion Dynamics Of Depressionmentioning
confidence: 99%
See 2 more Smart Citations